Molecular imprinting-based nanocomposite adsorbents for typical pollutants removal - Wang, Liyan; Yu, Jialuo; Wang, Xiaoyan; Li, Jinhua; Chen, Lingxin (Journal of hazardous materials letters, 2023)
Environment pollution as a worldwide issue calls for high-performance adsorbent materials for effective removal and remediation. Nanocomposites have come to the force to remove pollutants due to their superior adsorption performances from nanosize effect, combination-versatility, and inheritance/transcendence of the parent constituents. Among them, molecular imprinting-based nanocomposites with tailor-made binding sites complementary to target molecules have drawn great research interests in environmental pollutants removal due to the outstanding recognition selectivity. Herein, the general fabrication and typical components of molecular imprinting-based nanocomposite adsorbents are summarized. Furthermore, synthesis strategies taken to improve the adsorption performances of nanocomposites are presented to provide a backdrop for future research. [Display omitted] ●Nanocomposites are successful combinations of two or more nanomaterials to improve the overall adsorption performances.●Molecular imprinting-based nanocomposites with tailor-made binding sites provide outstanding recognition selectivity.●Nanocomposites offer a unique design platform due to great synthetic versatility from the smart combination of the parent components.●Strategies for improving the adsorption performances from design of interfacial characteristics, morphology and nanoscale structures.